Untimely Bollywood : globalization and India's new media assemblage - Rai, Amit, 1968- (e-Duke books scholarly collection., 2009)
"Known for its elaborate spectacle of music, dance, costumes, and fantastical story lines, Bollywood cinema is a genre that foregrounds narrative rupture, indeterminacy, and bodily sensation. In "Untimely Bollywood," Amit S. Rai argues that the fast-paced, multivalent qualities of contemporary Bollywood cinema are emblematic of the changing conditions of media consumption in a globalizing India. Through analyses of contemporary media practices, Rai shifts emphasis from a representational and linear understanding of the effects of audiovisual media to the multiple, contradictory, and evolving aspects of media events. He uses the Deleuzian concept of "assemblage" as the model for the complex clustering of technological, historical, and physical processes that give rise to contemporary media practices. Exploring the ramifications of globalized media, he sheds light on how cinema and other popular media organize bodies, populations, and spaces in order to manage the risky excesses of power and sensation and reinforce a liberalized postcolonial economy."--Book cover